Mechanisms of tumour vascularization in cutaneous malignant melanoma: clinical implications. (1st August 2014) - Pastushenko, I.; Vermeulen, P.B.; Van den Eynden, G.G.; Rutten, A.; Carapeto, F.J.; Dirix, L.Y.; Van Laere, S.
Summary: Malignant melanoma represents < 10% of all skin cancers but is responsible for the majority of skin‐cancer‐related deaths. Metastatic melanoma has historically been considered as one of the most therapeutically challenging malignancies. Fortunately, for the first time after decades of basic research and clinical investigation, new drugs have produced major clinical responses. Angiogenesis has been considered an important target for cancer treatment. Initial efforts have focused primarily on targeting endothelial and tumour‐related vascular endothelial growth factor signalling. Here, we review different mechanisms of tumour vascularization described in melanoma and discuss the potential clinical implications.